2018
DOI: 10.3920/wmj2018.2362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mitigation of aflatoxins in Kenya (1960-to date)

Abstract: Aflatoxins are highly toxic metabolites of several Aspergillus species widely distributed throughout the environment. These toxins have adverse effects on humans and livestock at a few micrograms per kilogram (μg/kg) concentrations. Strict regulations on the concentrations of aflatoxins allowed in food and feed exist in many nations in the developing world. Loopholes in implementing regulations result in the consumption of dangerous concentrations of aflatoxins. In Kenya, where ‘farm-to-mouth’ crops become sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 63 publications
(120 reference statements)
1
71
1
2
Order By: Relevance
“…The probable daily intake (PDI) of aflatoxin B1 in the country, via maize only, was recently estimated to vary between 0.07-60,612.00 ng/kg bw/day, with an average of 312.4 ng/kg bw/day) [80], which is alarming compared with an average of 10 to 200 ng/kg/day for the rest of the world [81], and with the conservative tolerable daily intake (TDI) of 0.11 to 0.19 ng/kg bw/day [82]. Incidentally, this country also ranks among the countries with the highest prevalence of oesophageal cancer, which was associated with aflatoxin intake as a risk factor [18,80,83]. Conversely, a recent survey on aflatoxin contamination of maize grown in eight different AEZs in Uganda revealed that the highest levels (a maximum of 3760 g/kg) and an average of 66.5 g/kg) were recorded in the zones with high rainfalls (1200->1400 mm); the percentage of samples exceeding the national regulatory standards of 10 g/kg reached 22.2% [84].…”
Section: Crop Contaminationmentioning
confidence: 99%
See 4 more Smart Citations
“…The probable daily intake (PDI) of aflatoxin B1 in the country, via maize only, was recently estimated to vary between 0.07-60,612.00 ng/kg bw/day, with an average of 312.4 ng/kg bw/day) [80], which is alarming compared with an average of 10 to 200 ng/kg/day for the rest of the world [81], and with the conservative tolerable daily intake (TDI) of 0.11 to 0.19 ng/kg bw/day [82]. Incidentally, this country also ranks among the countries with the highest prevalence of oesophageal cancer, which was associated with aflatoxin intake as a risk factor [18,80,83]. Conversely, a recent survey on aflatoxin contamination of maize grown in eight different AEZs in Uganda revealed that the highest levels (a maximum of 3760 g/kg) and an average of 66.5 g/kg) were recorded in the zones with high rainfalls (1200->1400 mm); the percentage of samples exceeding the national regulatory standards of 10 g/kg reached 22.2% [84].…”
Section: Crop Contaminationmentioning
confidence: 99%
“…Subsequently, Wicklow and Shotwell [16] confirmed the production of B and G aflatoxins by other strains of A. flavus; NRRL strains 3357, 6412, 6554, 6555, and 13003. Yet, the inability of A. flavus to produce the G aflatoxins was later reiterated and evidenced by genetic analysis relating indel (short insertions or deletions) mutations in the cypA/norB region in A. flavus to the impairment of the expression of genes coding for P450 monooxygenase enzyme required for the biosynthesis of G aflatoxins [17][18][19]. However, it was argued that this mutation does not occur in all strains, and some A. flavus strains can still produce B or G aflatoxins depending on the morphotype (S or L) and on the phylogenetic group (I or II) to which they belong.…”
Section: Aflatoxin-producing Molds: Taxonomical Elementsmentioning
confidence: 99%
See 3 more Smart Citations